The Hero's Journey of Evelyn Wang in Everything Everywhere All at Once (2022) Film - Jesika Jesika; Eka Pratiwi Sudirman (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This research focuses on finding out the hero’s journey of the main character, Evelyn Wang, seen in Everything Everywhere All at Once (2022) film. This research used Christopher Vogler’s hero’s journey theory to find out how Wang passed all the hero’s journey stages to finally become a hero. Qualitative method and structuralism approach were used in this research. The data taken in this research is in the form of words, phrases, sentences, dialogues, images, and actions which are seen throughout the film that indicate the hero’s journey of Wang. The result of this research reveals that Wang went through all 12 stages of the hero’s journey by Vogler and her journey is most likely unique. Unlike typical heroes that conquer their enemies through destruction, Wang’s journey focuses on self-acceptance, love, and finding meaning in an overwhelming world. By embracing her chaotic life experience, she becomes a hero not through physical strength, but through understanding and human connection. This is represented through her transformation from a stressed and overwhelmed woman who constantly fear to face her problems, to a courageous individual who embraces her difficulties with acceptance and understanding, illustrating her growth into a true hero.